Comparative genomics analyses of fish pathogenic Streptococcus spp. isolated from tilapia and flounder (Annals of Bangladesh Agriculture, 2023)
This comparative study was performed to analyze the whole genome sequences of three species of Streptococcus (S. agalactiae, S. iniae and S. parauberis) isolated from Tilapia and Flounder from six different countries (Brazil, China, Israel, South Korea, Taiwan and USA). The objectives were to compare the genomic features, virulence, and antibiotic resistance genes in the genome sequences of 11 isolates of Streptococcus spp. A total of 44 virulence genes were identified in the genomes of 11 strains. These genes are responsible for adherence, various enzyme production, immune evasion, immunoreactive antigen, and toxin production. Eight antibiotic resistance genes were identified in the eleven genome sequences of the Streptococcus sp. strains. All strains of S. agalactiae and S. iniae harbor macrolide resistance gene mreA. Although five secondary metabolites such as Arylpolyene (ary), Type III Polyketide synthases (T3PKS), RiPP-like peptide, linear azol(in)e-containing peptides (LAPs), RaS-RiPP antimicrobial compound, and T3PKS were detected in all 11 genomes; only T3PKS was common in all strains. Additionally, Cas cluster CAS-TypeIC and CAS-TypeIIA were identified among the ten strains of S. agalactiae and S. iniae. The findings indicated that the degree of pathogenicity of Streptococcus sp. remained closer regardless of origin, distribution and host. The results would be useful to understand the virulence factors of the Streptococcus sp. and the antibiotic resistance genes associated with their virulence in fish. Ann. Bangladesh Agric. (2023) 27 (2): 1-18